Manajemen Pendidikan Anak Menurut Hadits Rasulullah Tentang Ibu - Wahyudi Widodo (Departement of Mathematics Education, 2024)
A godly child is one who devotes himself to one's parents and an ungodly son is a disobedient child to one's parents. Parental guidance and direction until it becomes successful if it is done well. One of them is related to mothers, because mothers are the main conscience of children's education so that management is important for a mother. The research method used is a library with a descriptive type. The result is that the hadith mentions Mother three times (3X) than father is hinting at the importance of mother. Where a mother struggles from the time of pregnancy to adulthood. For example, related to breast milk which is very important than formulas and others where everything is in the hands of a strong mother. Therefore, management for a mother is important by paying attention to the hadith of the Messenger of Allah. The management is divided into three, namely planning, organizing and also implementing. However, in this management, a mother also needs communication with her husband or father of her child so that the management is carried out properly, especially if the mother works, of course, it takes more time in educating children but still doing their job.